Parkinson's disease and the gut: Models of an emerging relationship. (15th September 2021) - Bindas, Adam J.; Kulkarni, Subhash; Koppes, Ryan A.; Koppes, Abigail N.
Abstract: Parkinson's disease (PD) is a common neurodegenerative disease characterized by a progressive loss of fine motor function that impacts 1-2 out of 1, 000 people. PD occurs predominately late in life and lacks a definitive biomarker for early detection. Recent cross-disciplinary progress has implicated the gut as a potential origin of PD pathogenesis. The gut-origin hypothesis has motivated research on gut PD pathology and transmission to the brain, especially during the prodromal stage (10-20 years before motor symptom onset). Early findings have revealed several possible triggers for Lewy pathology – the pathological hallmark of PD – in the gut, suggesting that microbiome and epithelial interactions may play a greater than appreciated role. But the mechanisms driving Lewy pathology and gut-brain transmission in PD remain unknown. Development of artificial α-Synuclein aggregates (α-Syn preformed fibrils) and animal disease models have recapitulated features of PD progression, enabling for the first time, controlled investigation of the gut-origin hypothesis. However, the role of specific cells in PD transmission, such as neurons, remains limited and requires in vitro models for controlled evaluation and perturbation. Human cell populations, three-dimensional organoids, and microfluidics as discovery platforms inch us closer to improving existing treatment for patients by providing platforms for discovery and screening. This review includes a discussion of PD pathology, conventional treatments, in vivo and in vitro models, and future directions. Statement of significance: Parkinson's Disease remains a common neurodegenerative disease with palliative versus causal treatments. Recently, the gut-origin hypothesis, where Parkinson's disease is thought to originate and spread from the gut to the brain, has gained traction as a field of investigation. However, despite the wealth of studies and innovative approaches to accelerate the field, there remains a need for in vitro tools to enable fundamental biological understanding of disease progression, and compound screening and efficacy. In this review, we present a historical perspective of Parkinson's Disease pathogenesis, detection, and conventional therapy, animal and human models investigating the gut-origin hypothesis, in vitro models to enable controlled discovery, and future outlooks for this blossoming field. Graphical abstract: Image, graphical abstract